AB0788 Epidemiology of systemic sclerosis in sardinia. analysis of hospitalization data in the decade 2001-2010. (23rd January 2014) - Sanna, S.; Casula, L.; Perra, D.; Piga, M.; Antonelli, A.; Mathieu, A.
Abstract : Background: Over the past decade, several advances in the management of Systemic Sclerosis (SSc) have occurred that may affect hospitalization patterns 1 . Major causes of hospitalization for SSc patients are periodic intravenous treatment, management of typical manifestations and complications or coexisting medical conditions. Objectives: The aim of the study was to quantify the burden of SSc in Sardinia, an autonomous region of Italy with about 1.600.000 residents, with particular emphasis on the access to health services, through a population-based study analyzing hospitalization data in the decade 2001-2010. Methods: The study was performed on data regarding the hospital discharge records (SDO) with a diagnosis of SSc, identified by the ICD-9-CM code (710.1), in the field of both principal (defined as the condition chiefly responsible for the hospitalization) and secondary diagnosis, The SDO data were obtained from the Department of Hygiene and Health of the "Regione Autonoma della Sardegna". The abstracted data allowed to be aware of the number of patients hospitalized but not repeat hospitalizations of individuals to be known. All the hospitalizations of SSc patients have been analyzed according to sex, age (0-16 yrs; 17-24 yrs; 25-44 yrs; 45-64 yrs; >65 yrs), types of admission to hospital (in-patient and day-hospital), length of stay or number of accesses. Results: The study included 4.144 hospitalizations in 624 patients. SSc was the principal diagnosis in 2.916 hospitalization (70.4%). The 49.7% of hospitalization occurred in patients aged 45-64 years and involved women in 84.7% of admissions. During the study period an increasing trend in the number of hospitalizations with SSc as the principal discharge diagnosis, has been observed (from 148 in 2001 to 427 in 2010), whileit remained stable for those with secondary diagnosis. The overall mean length of stay for in-patient hospitalizations were 8.3 days (standard deviation ± 5.7; median 7 days) and 8.5 days (standard deviation ± 9.4; median 6 days) for SSc as a principal and secondary discharge diagnosis, respectively. After stratification for the type of admission the 68% of hospitalizations resulted as in-patient care and the 32% as day-hospital (a programmed one day hospitalization). The in-patient/day-hospital ratio decreased from 3.5:1 in 2001 to 1.3:1 in 2010. Between 2001 and 2010 the hospitalizations with SSc as the principal discharge diagnosis were 0.8 per 1.000, considering all the admission with any diagnosis in the Regional area. The numberof patients admittedin thedecade was 624: 84% women and 16% men (F:M ratio 5.4:1). The largest proportion of patients (42.3%) were aged 45-64 years, followed by those aged >65 years (37.5%). Conclusions: This study suggests that between 2001 and 2010 the hospitalization patterns has changed with greater need of day-hospital admission and an increase in the number of access. This may beattributableto an increase ofhospitalization for intravenoustreatmentwith prostanoids and a decrease of systemic complications. References: Chung L, et al. Hospitalizations and mortality in systemic sclerosis: results from the Nationwide Inpatient Sample . Rheumatology (Oxford). 2007;46:1808-13. Disclosure of Interest: None Declared